Battery black spot detection method and application thereof in battery self-discharge abnormity analysis

By using metallurgical glue to wrap the battery black spot sample and cut it, the problem of inaccurate cutting position in the prior art caused by too small black spots is solved, and higher detection accuracy and efficiency are achieved, and it is suitable for battery samples with small black spot areas.

CN119715645APending Publication Date: 2025-03-28EVE ENERGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411815137.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When cutting the black spot cross-section of the battery with CP plasma beam, the cutting position is inaccurate due to the small black spot, resulting in sample production failure and affecting the analysis results.

Method used

Metallurgy liquid is used to wrap the battery black spot sample, cut and polish the solid after metallographic solids, and characterize the cross-sections in combination with scanning electron microscopy and X-ray energy spectrum analysis.

Benefits of technology

It improves the accuracy of the cutting position and is suitable for battery black dot samples with small black dot areas, reducing the risk of sample production failure, improving detection accuracy and efficiency, and safely preparing the sample process, avoiding the use of low-temperature equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119715645A_ABST
    Figure CN119715645A_ABST
Patent Text Reader

Abstract

The invention provides a battery black spot detection method and application thereof in battery self-discharge abnormity analysis. The method comprises the following steps: S1, preparing a metallographic glue solution from metallographic glue powder and a metallographic curing agent; s2, the battery black spot sample is immersed in a metallographic phase glue solution, the metallographic phase glue solution is solidified to wrap the battery black spot sample, a metallographic phase solid is obtained, and the area of black spots in the battery black spot sample is smaller than or equal to 10 <-4 > cm < 2 >; and S3, representing the cross section of the battery black spot sample in the metallographic solid by combining a scanning electron microscope and X-ray energy spectrum analysis. According to the method, the metallographic solid is prepared from the metallographic glue solution and the black spot sample and then is cut, so that the risk that the analysis result is influenced by sample preparation failure caused by inaccurate cutting position due to too small black spot area is reduced, the battery black spot sample is analyzed by combining SEM and EDS, the sample preparation cost is low, the sample preparation efficiency is high, and the detection and test precision is high; the requirement on black spot size is low, the sample preparation success rate is high, and the sample preparation process is safe.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a battery black spot detection method and its application in battery self-discharge anomaly analysis. Background Art

[0002] Lithium-ion batteries are widely used in many occasions due to their good comprehensive performance. However, due to abnormal self-discharge, the consistency of the battery pack deteriorates, and excessive use occurs during the charging and discharging process, which ultimately leads to performance degradation and shortened cycle life. Therefore, self-discharge plays a key role in evaluating battery performance. The storage, transportation, and life of lithium-ion batteries are directly related to battery self-discharge.

[0003] The factors that cause abnormal self-discharge of lithium-ion batteries are mainly divided into two categories: physical self-discharge and chemical self-discharge. Among them, the main cause of physical self-discharge is the micro-short circuit inside the battery caused by metal impurities and dust particles, which significantly reduces the battery voltage. After disassembling the battery with abnormal self-discharge, abnormal black spots are usually observed on the battery diaphragm. Therefore, by observing and measuring the number, morphology, size, elemental composition, etc. of the black spots on the diaphragm, the magnitude of the battery's physical self-discharge and its possible causes can be determined.

[0004] At present, the common method for detecting black spots is to use ion beam profile polishing and ion beam cross-section polishing (CP for short). This method mainly uses CP plasma beam to cut the black spot section and then detect and analyze the section. The cutting temperature needs to be carried out in a low temperature environment. When the equipment accuracy is limited and the diaphragm black spot is too small, the cutting position may be inaccurate, resulting in sample preparation failure and affecting the analysis results. Summary of the invention

[0005] In order to solve the problem that when cutting the black spot cross section using CP plasma beam, the cutting position is inaccurate due to the black spot being too small, resulting in sample preparation failure and affecting the analysis results, the present application provides a battery black spot detection method and its application in battery self-discharge abnormality analysis.

[0006] According to a first aspect of the present application, a battery black spot detection method is provided, comprising the following steps:

[0007] S1. A metallographic glue solution is prepared by using metallographic glue powder and a metallographic curing agent;

[0008] S2. Immerse the battery black spot sample in metallographic glue, and allow the metallographic glue to solidify to wrap the battery black spot sample to obtain a metallographic solid, wherein the black spot area in the battery black spot sample is ≤10 -4 cm 2 For example, the area of ​​the black spot in the battery black spot sample can be 10-4 cm 2 , 10 -5 cm 2 , 10 -7 cm 2 , 10 -8 cm 2 , but not limited to the listed values, other values ​​not listed in the numerical range are also applicable;

[0009] S3. Combine scanning electron microscopy and X-ray energy spectrum analysis to characterize the cross-section of battery black spot samples in metallographic solids.

[0010] In the battery black spot detection method provided in the present application, the battery black spot sample is first immersed in a metallographic glue, and after the metallographic glue solidifies, the battery black spot sample is wrapped therein to obtain a metallographic solid, and the cross section of the battery black spot sample is obtained from the metallographic solid by cutting or grinding, and then the cross section is analyzed by scanning electron microscopy (SEM) and X-ray energy spectrum analysis (EDS). First, compared with directly using ion beam profile grinding and ion beam cross-section grinding (CP) to cut the battery black spot sample to obtain a cross section and then analyze it, the detection method provided in the present application uses the metallographic glue to solidify and then wrap the battery to obtain a metallographic solid and then cut it. This method makes the cutting position more accurate, especially suitable for battery black spot samples with a small black spot area (black spot area ≤10 -4 cm -2 ), which is beneficial to reduce the risk of sample preparation failure caused by inaccurate cutting position due to the small black spot area, thereby affecting the analysis results. Second, after obtaining the cross-section of the battery black spot sample in the above manner, the microscopic morphology of the cross-section is tested using SEM, and the depth and state of foreign matter penetration on the cross-section of the battery black spot sample can be clearly observed. In combination with EDS, the metal element composition on the cross-section of the battery black spot sample is tested, thereby achieving the purpose of analyzing the battery black spot sample. Third, compared with CP plasma beam cutting, the battery black spot detection method provided in the present application has lower production costs and faster sample preparation efficiency. The sample preparation time is 5 hours faster than CP plasma beam cutting (6 hours), and the detection and testing accuracy is high. The element depth distribution of the black spots on the cross-section can be accurately identified, the requirements for the black spot size are low, the sample preparation success rate is high, and the sample preparation does not require the preparation of low-temperature dangerous supplies such as liquid nitrogen, and the sample preparation process is safe.

[0011] Preferably, in S1, the mass ratio of metallographic glue powder to metallographic curing agent is 1:1-2. For example, the mass ratio of metallographic glue powder to metallographic curing agent can be 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0012] By controlling the mass ratio of the metallographic glue powder and the metallographic curing agent used to prepare the metallographic glue within the above range, on the one hand, the generation of internal bubbles in the metallographic solid can be reduced to ensure the smoothness of the metallographic solid; on the other hand, the metallographic glue can be better mixed with the battery black spot sample, and the prepared metallographic solid can maintain a lighter color for easy observation. Through the above two effects, the accuracy of the detection results of the battery black spot samples can be improved.

[0013] If the content of metallographic curing agent used to prepare metallographic glue is too much, it will cause more bubbles inside the metallographic solid and the interior will be uneven. If the content of metallographic glue powder used to prepare is too much, the hardness of the prepared metallographic glue will be too high, making the metallographic glue and the prepared metallographic solid darker in color and inconvenient to observe. The hardness of the prepared metallographic glue is too high and it is difficult to mix metallographically with the battery black spot sample.

[0014] Preferably, S1 comprises the following operating steps: mixing metallographic glue powder and metallographic curing agent to obtain a mixed solution, stirring the mixed solution until the mixed solution becomes milky white, stopping stirring, cooling, and obtaining a metallographic glue solution.

[0015] In the process of preparing metallographic glue liquid using metallographic glue powder and metallographic curing agent, the metallographic glue powder and metallographic curing agent need to be stirred to make the mixed liquid milky white to successfully prepare. If the metallographic glue powder and metallographic curing agent need to be stirred to make the mixed liquid transparent after mixing, it means that the stirring is excessive and the preparation of the metallographic glue liquid fails. Using transparent metallographic glue liquid to prepare metallographic solid will affect the preparation of metallographic solid and the final test results of battery black spot samples.

[0016] Preferably, in S1, the cooling operation time is 5 to 15 minutes. For example, the cooling operation time can be 5 minutes, 7 minutes, 9 minutes, 11 minutes, 13 minutes, or 15 minutes, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0017] The cooling time after the metallographic glue powder and the metallographic curing agent are mixed and stirred until the mixed solution becomes milky white is controlled within the above range, so that the prepared metallographic glue solution can be better mixed with the battery black spot sample.

[0018] If the cooling time after the metallographic glue powder and the metallographic curing agent are mixed and stirred until the mixture becomes milky white is too long, the metallographic glue will gradually solidify into a solid, making it difficult to mix the metallographic glue with the battery black spot sample metallographically.

[0019] Preferably, S2 includes the following operations: immersing the battery black spot sample in metallographic glue, cooling for 25 to 35 minutes, and obtaining a metallographic solid. For example, the cooling time can be 25 minutes, 27 minutes, 29 minutes, 31 minutes, 33 minutes, or 35 minutes, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0020] After immersing the battery black spot sample in the metallographic glue, the cooling time is controlled within the above range, so that a metallographic solid with moderate hardness can be obtained, which is conducive to subsequent cutting and polishing, and thus better detection and analysis of the cross section of the battery black spot sample.

[0021] If the cooling time after immersing the battery black spot sample in the metallographic glue is too short, the hardness of the metallographic solid will be too low, affecting the subsequent cutting and polishing, and may cause the failure of obtaining the cross section of the battery black spot sample, thereby affecting the final detection and analysis results.

[0022] Preferably, in S3, the cross section of the battery black spot sample is prepared by the following steps: using sandpaper to grind the metallographic solid along a direction perpendicular to the battery black spot sample to obtain the cross section of the battery black spot sample.

[0023] Preferably, in S3, the mesh number of the sandpaper is ≥3000 mesh. For example, the mesh number of the sandpaper can be 3000 mesh, 3500 mesh, 4000 mesh, 4500 mesh, or 5000 mesh, but is not limited to the listed values. Other values ​​not listed within the numerical range are also applicable.

[0024] Preferably, in S3, the rotation speed of the grinding operation is 550-650 rpm / min. For example, the rotation speed of the grinding operation can be 550 rpm / min, 570 rpm / min, 590 rpm / min, 610 rpm / min, 630 rpm / min, 650 rpm / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] In the process of grinding metallographic solids with sandpaper, using sandpaper with a mesh size of 3000 or more and controlling the grinding operation speed within the above range can make the cross-section of the battery black spot sample after grinding more flat and smooth, and the position of the cross-section of the battery black spot sample can be accurately grasped by speed control, so that the obtained cross-section is more suitable for subsequent SEM / EDS detection.

[0026] If the grinding operation rotates too fast, it will be difficult to grasp the accuracy of the battery black spot sample. The faster the rotation speed, the more likely it is that the cross section of the part used for testing will be polished and cleaned, making it impossible to obtain samples for testing.

[0027] Preferably, the battery black spot samples include at least one of diaphragm black spots and pole piece black spots.

[0028] According to a second aspect of the present application, there is provided an application of the battery black spot detection method in battery self-discharge anomaly analysis.

[0029] During battery failure analysis, both abnormal and normal batteries can be disassembled to reveal black spots on the diaphragm, and metal elements can be tested on the surface. At this time, it is impossible to determine whether the abnormal battery self-discharge voltage drop is caused by a micro-short circuit of the metal black spots. Since metals are conductive, the metal inside the diaphragm will conduct the diaphragm that originally blocked electrons, thereby causing conduction between the positive and negative electrodes, which is one of the reasons that affect battery self-discharge. In order to study whether the black spots on the diaphragm affect the self-discharge of the battery, it is usually necessary to test and analyze the elemental composition of the cross section of the black spots on the diaphragm, mainly to observe whether there are metal elements at different depths of the entire cross section of the black spots on the diaphragm. It can be determined whether the metal elements grow inward from the surface of the diaphragm to the other side, thereby confirming that the black spots on the diaphragm precipitate through the metal outside-inside-outside of the diaphragm to form an electric potential path to form a micro-short circuit, thereby causing abnormal battery self-discharge.

[0030] Therefore, the battery black spot detection method provided in the present application is applied to the analysis of battery self-discharge anomaly. By analyzing the depth, morphological characteristics and elemental content composition of the black spots on the surface of the diaphragm penetrating and growing into the interior of the diaphragm, the purpose of analyzing the cause of the battery self-discharge anomaly is achieved, and then it is determined whether the battery self-discharge anomaly is caused by micro-short circuits formed by metal in the black spots on the diaphragm, which provides a simple, fast and more accurate detection method for battery self-discharge anomaly analysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a graph of the observation results of Example 2 under a three-dimensional microscope (metallographic microscope) at high magnification, after the metallographic solid containing diaphragm black spots was polished with sandpaper using the detection method provided in Example 1.

[0032] Figure 2 This is a result diagram of observing the morphology of the black spot cross section of the diaphragm using SEM provided in Example 2.

[0033] Figure 3 This is a graph showing the results of using EDS to detect the metal elements in the black spot cross section of the diaphragm provided in Example 2.

[0034] Figure 4 This is a result diagram of observing the cross-section morphology of black spots on the negative electrode sheet using SEM provided in Example 3.

[0035] Figure 5 This is a graph showing the results of using EDS to detect the metal elements in the black spot cross section of the negative electrode sheet provided in Example 3.

[0036] Figure 6 This is a result diagram of observing the cross-section morphology of the black spots on the negative electrode sheet using SEM, provided for comparative example 2.

[0037] Figure 7 This is a graph showing the results of using EDS to detect the metal elements in the black spot cross section of the negative electrode sheet provided for comparative example 2. DETAILED DESCRIPTION

[0038] The following is a further clear and complete description of the technical features in the technical solution provided by this application in conjunction with the specific implementation methods. Obviously, the described embodiments are only part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of this application.

[0039] Example 1

[0040] A battery black spot detection method comprises the following steps:

[0041] S1. Mix the metallographic glue powder and the metallographic curing agent in a mass ratio of 1:1.5, stir the mixture until it changes from light yellow to milky white, stop stirring, and cool for 10 minutes to obtain a metallographic glue solution;

[0042] S2. Disassemble the battery black spot samples from the abnormally charged and discharged batteries and cut them into squares, pour the cooled metallographic glue into the prepared square mold, pour the metallographic glue into half of the mold volume, then put the battery black spot sample in, so that the battery black spot sample floats on the surface of the metallographic glue, then add the metallographic glue to completely immerse the mold, cool for 30 minutes to solidify the metallographic glue, and obtain a metallographic solid;

[0043] S3. Take out the square metallographic solid, use a cutting machine to cut the excess part of the metallographic solid, put the cut metallographic solid into a metallographic polisher and polish the metallographic solid with sandpaper of 3000 mesh or more at a speed of 600 rpm / min to obtain the cross section of the battery black spot sample in the metallographic solid and characterize the cross section with scanning electron microscopy (SEM) and X-ray energy spectrum analysis (EDS), wherein the polishing position needs to be perpendicular to the black spot placement surface of the battery sample.

[0044] Example 2

[0045] This embodiment aims to use the detection method provided in Example 1 to detect black spots (black spot area ≤ 10 -4 cm 2) was tested and analyzed, wherein the black spot cross section obtained by grinding the metallographic solid containing the diaphragm black spot with sandpaper under a three-dimensional microscope (metallographic microscope) with high magnification was observed as follows Figure 1 As shown in the figure, the results of SEM observation of the morphology of the black spot cross section of the diaphragm are as follows Figure 2 As shown in the figure, the results of using EDS to detect the metal elements in the black spot section of the diaphragm are as follows Figure 3 As shown, in order to avoid measurement errors, the EDS scanning depth is set to 3μm, where Figure 3 A represents the EDS line scan spectrum, Figure 3 B represents the EDS spectrum data diagram.

[0046] Depend on Figure 1 It can be seen that the battery black spot detection method provided in Example 1 can be used to prepare a metallographic solid containing diaphragm black spots, and the diaphragm black spot sample can be accurately cut through polishing to obtain the diaphragm black spot cross section for subsequent detection.

[0047] Depend on Figure 2 It can be seen from the SEM observation that foreign matter has penetrated into the black spots of the separator of the abnormal self-discharge battery used for the test in this embodiment, and the foreign matter has penetrated from the surface of the black spots of the separator into the inside of the separator.

[0048] Depend on Figure 3 It can be seen that the Ni element exists in the entire cross-section of the black spots on the diaphragm of the abnormal self-discharge battery tested in this embodiment, which proves that the metal not only accumulates on the surface of the diaphragm, but also penetrates into the diaphragm, causing the positive and negative electrodes to be connected, thereby causing abnormal self-discharge of the battery cell.

[0049] Example 3

[0050] This embodiment aims to dismantle the negative electrode sheet black spots in the battery with abnormal self-discharge and use the detection method provided in Example 1 to detect the negative electrode sheet black spots (black spot area ≤ 10 -4 cm 2 ) was tested and analyzed, wherein the results of observing the morphology of the cross section of the negative electrode sheet black spot using SEM are as follows Figure 4 As shown in the figure, the results of using EDS to detect the metal elements in the black spot cross section of the negative electrode are as follows Figure 5 As shown, in order to avoid measurement errors, the EDS scanning depth is set to 3μm, where Figure 5 A represents the EDS line scan spectrum, Figure 5 B represents the EDS spectrum data diagram.

[0051] Depend on Figure 4It can be seen that in the process of detecting the black spots on the negative electrode sheets disassembled from the abnormal self-discharge batteries using the detection method provided in Example 1, the intermediate layer Cu current collector is polished and deformed due to polishing, but this does not affect the final analysis results. Through SEM observation, it can be found that foreign matter has penetrated into the black spots on the negative electrode sheets of the abnormal self-discharge batteries used for the test in this embodiment, and the foreign matter has penetrated from the surface of the black spots on the negative electrode sheets into the interior of the negative electrode sheets.

[0052] Depend on Figure 5 It can be seen that the Ni element exists in the entire cross-section of the black spots on the negative electrode sheet of the abnormal self-discharge battery used for the test in this embodiment, which means that the Ni metal is not only gathered on the surface of the negative electrode sheet but has penetrated into the inside of the negative electrode sheet. Therefore, it is judged that the black spots are not caused by metal dust introduced during the process, and further effective investigation of abnormal conditions such as metal impurities is required.

[0053] Comparative Example 1

[0054] This comparative example provides a battery black spot detection method, which mainly uses a CP plasma beam to cut the black spot cross section and then detect and analyze the cross section. The method refers to Chinese patent CN 115901317A and specifically includes the following steps:

[0055] S1. Obtain an abnormal battery, disassemble its diaphragm or negative electrode sheet, and dry the diaphragm or negative electrode sheet;

[0056] S2. Cut the abnormal area with black spots on the separator or negative electrode sheet so that the side with black spots faces upward, and attach it to the conductive adhesive, and then make a pre-cut surface at the location of the black spots on the separator or negative electrode sheet. The pre-cut surface must be flat and burr-free to ensure the subsequent cutting effect. The location of the pre-cut surface is near the black spots to ensure that the subsequent cutting surface can accurately cut the black spots;

[0057] S3. Fix the diaphragm or negative electrode sheet with a pre-cut surface on the baffle, and make the black spot in the middle of the cutting, and then make the cutting surface along the pre-cut surface by ion beam cutting. During the cutting process, the cutting environment is cooled by liquid nitrogen to prevent the diaphragm or negative electrode sheet from melting. After the cutting is completed and the temperature rises, the cutting surface and the baffle are sprayed with gold;

[0058] The ion beam cutting process mainly includes: placing the diaphragm or the negative electrode sheet into the argon ion beam cross-section cutting instrument, setting the parameters and cutting mode, and then performing cross-section cutting. During the cutting process, the cutting voltage is 4KV, the cutting time is 4h, and liquid nitrogen is used for cooling at the same time, so that the ambient temperature during the cutting process is not higher than -80°C. After the cutting is completed and the temperature rises, the sample is taken out, and the cutting surface and the baffle are sprayed with gold together;

[0059] S4. Perform microscopic morphology test on the cut surface of the separator or negative electrode sheet by SEM, obtain the cross-sectional morphology of the black spots of the separator or negative electrode sheet, measure and analyze it, and perform EDS spectrum test on the cut surface;

[0060] S5. Measure and analyze the cross-sectional morphology and energy spectrum data of black spots on the diaphragm or negative electrode to assist in determining the degree of battery self-discharge and the cause.

[0061] Comparative Example 2

[0062] This comparative example aims to use the detection method provided in comparative example 1 to detect the black spots (black spot area ≤ 10 -4 cm 2 ) was tested and analyzed, and the results of observing the morphology of the cross section of the negative electrode black spot using SEM are as follows Figure 6 As shown in the figure, the results of using EDS to detect the metal elements in the black spot cross section of the negative electrode are as follows Figure 7 shown.

[0063] Depend on Figure 6 From the SEM results, it can be seen that the cross-section of the black spots on the negative electrode sheet after cutting them with the CP plasma beam is intact, without any physical damage. The Si particles and C particles can be accurately identified by SEM, and the negative electrode powder and the current collector are clearly distributed. It can be seen that the interface of the black spot cross-section obtained by cutting the black spots on the negative electrode sheet with the CP plasma beam is relatively clear.

[0064] Depend on Figure 7 The EDS test results show that the method provided in Comparative Example 1 can only detect the presence of metal elements on the surface of the negative electrode sheet, but no metal elements are detected at different depths. In addition, the black spot sample of the negative electrode sheet is a special sample containing metal elements that have penetrated into the negative electrode sheet. However, since the area of ​​the black spot in the negative electrode sheet is ≤10 -4 cm 2 After the sample was prepared by the method of comparative example 1, no metal elements were identified in different depths by EDS. - 4 cm 2 Using CP for sample preparation testing cannot effectively identify the penetration of the black spot elements of the negative electrode sheet at one time, so it is impossible to accurately analyze and determine whether the black spots of the negative electrode sheet exist in a particle state embedded in the surface (due to dust) or are deposited and gathered on the surface of the negative electrode sheet by reaching the redox potential (due to incoming materials).

[0065] If the test is accurate and can effectively identify the source of the black spots on the diaphragm or negative electrode at one time, it is possible to effectively distinguish whether the source of the black spots on the diaphragm or negative electrode is dust particles or metal impurities.

[0066] Comparing the test results finally obtained by the test methods provided in Comparative Example 1 and Example 1, it can be seen that the test method provided in Comparative Example 1 is effective in detecting black spot areas ≤10 -4 cm 2 When preparing the negative electrode sheet, the test cannot effectively identify the source of the black spots on the negative electrode sheet at one time because CP is used for sample preparation. The detection method provided in Example 1 uses a metallographic glue solution to solidify and then wrap the battery to obtain a metallographic solid before cutting. This method makes the cutting position more accurate, so that the black spot area of ​​the battery black spot sample is less than 10 -4 cm 2 In this case, the sample can still be successfully prepared and accurately cut to obtain the negative electrode sheet black spot cross section, so that the test can effectively identify the source of the negative electrode sheet black spots at one time, thereby achieving the purpose of effective detection and analysis of the black spot cross section.

[0067] In summary, the detection method provided in Comparative Example 1 refers to the CP sample preparation method of the diaphragm, and directly uses the CP plasma beam to cut the cross-section of the black spots on the negative electrode sheet, and then detects and analyzes the cross-section. When the equipment accuracy is limited and the black spots of the diaphragm & negative electrode sheet are too small, the cutting position may be inaccurate, resulting in failure of sample preparation, affecting the analysis results. In Examples 2 to 3, the battery black spot detection method provided in Example 1 is used when detecting the black spots on the battery diaphragm and the black spots on the negative electrode sheet. The battery black spot sample is first immersed in a metallographic glue solution. After the metallographic glue solution solidifies, the battery black spot sample is wrapped therein to obtain a metallographic solid. The cross-section of the battery black spot sample is obtained from the metallographic solid by cutting or polishing, and then the cross-section is analyzed by scanning electron microscopy (SEM) and X-ray energy spectrum analysis (EDS). First, compared with directly using ion beam profile grinding and ion beam cross-section grinding (CP) to cut the battery black spot sample to obtain a cross-section and then analyze it, the detection method provided in the present application uses the metallographic glue solution to solidify and then wrap the battery to obtain a metallographic solid. The method is to cut the battery black spot sample after it has solidified. This method makes the cutting position more accurate, which is especially suitable for battery black spot samples with a small black spot area. It is beneficial to reduce the risk of sample preparation failure caused by inaccurate cutting position due to the small black spot area, thereby affecting the analysis results. Second, after obtaining the cross-section of the battery black spot sample in the above manner, the microscopic morphology of the cross-section is tested using SEM, and the depth and state of foreign matter penetration on the cross-section of the battery black spot sample can be clearly observed. In combination with EDS, the metal element composition on the cross-section of the battery black spot sample is tested, thereby achieving the purpose of analyzing the battery black spot sample. Third, compared with CP plasma beam cutting, the battery black spot detection method provided in the present application has a lower production cost and faster sample preparation efficiency. The sample preparation time is 5 hours faster than CP plasma beam cutting (6 hours). The detection and testing accuracy is high, and the element depth distribution of the cross-section black spots can be accurately identified. The requirements for the black spot size are low, the sample preparation success rate is high, and the sample preparation does not require the preparation of low-temperature dangerous supplies such as liquid nitrogen, and the sample preparation process is safe.

[0068] The above embodiments are only used to illustrate the technical solution of the present application rather than to limit the protection scope of the present application. Although the present application is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solution of the present application can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present application.

Claims

1. A battery black spot detection method, characterized in that: The following steps are involved: S1. A metallographic glue solution is prepared by using metallographic glue powder and a metallographic curing agent; S2. Immerse the battery black spot sample in the metallographic glue, and allow the metallographic glue to solidify to wrap the battery black spot sample to obtain a metallographic solid, wherein the black spot area in the battery black spot sample is ≤10 -4 -2 cm; S3. Characterize the cross section of the battery black spot sample in the metallographic solid by combining scanning electron microscopy and X-ray energy spectrum analysis.

2. The battery black spot detection method according to claim 1, characterized in that: In S1, the mass ratio of the metallographic glue powder to the metallographic curing agent is 1:1-2.

3. The battery black spot detection method according to claim 1, characterized in that: The S1 comprises the following operation steps: mixing the metallographic glue powder and the metallographic curing agent to obtain a mixed solution, stirring the mixed solution until the mixed solution becomes milky white, stopping stirring, cooling, and obtaining the metallographic glue solution.

4. The battery black spot detection method as claimed in claim 3, characterized in that: In S1, the cooling operation time is 5 to 15 minutes.

5. The battery black spot detection method according to claim 1, characterized in that: The S2 comprises the following operations: immersing the battery black spot sample in the metallographic glue solution, cooling for 25 to 35 minutes, and obtaining the metallographic solid.

6. The battery black spot detection method according to claim 1, characterized in that: In S3, the cross section of the battery black spot sample is prepared by the following steps: using sandpaper to grind the metallographic solid along a direction perpendicular to the battery black spot sample to obtain the cross section of the battery black spot sample.

7. The battery black spot detection method as claimed in claim 6, characterized in that: In S3, the mesh number of the sandpaper is ≥3000 meshes.

8. The battery black spot detection method as claimed in claim 6, characterized in that: In S3, the grinding operation has a rotation speed of 550-650 rpm / min.

9. The battery black spot detection method according to claim 1, characterized in that: The battery black spot sample includes at least one of diaphragm black spots and pole piece black spots.

10. Application of the battery black spot detection method according to any one of claims 1 to 9 in battery self-discharge anomaly analysis.

Citation Information

Patent Citations

  • Lithium battery diaphragm black spot detection method

    CN115901317A